Governance and sustainability in information systems. Managing the transfer and diffusion of IT IFIP WG 8.6 International Working Conference, Hamburg, Germany, September 22-24, 2011. Proceedings - Nüttgens, Markus; Gadatsch, Andreas; Kautz, Karlheinz; Schirmer, Ingrid; Blinn, Nadine (Springer, 2011)
This book constitutes the refereed proceedings of the IFIP WG 8.6 International Working Conference on Governance and Sustainability in Information Systems, held in Hamburg, Germany, in September 2011. The 14 revised full papers and 16 research in progress and practice papers presented were carefully reviewed and selected from 47 submissions. The full research papers are organized in the following topical sections:governance, sustainability, design themes, customer and user integration, and future subjects.